1994
DOI: 10.1111/j.1365-2478.1994.tb00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity measurements on the sea bottom to map fracture zones in the bedrock underneath sediments1

Abstract: Refraction seismics with the shotpoints and the hydrophone cable on the seabottom, have become the standard geophysical method for investigating rock quality before constructing offshore tunnels in Norway. In connection with the construction of a sub-sea tunnel by the Norwegian Public Roads Administration, research work was carried out to compare two low-velocity zones, indicated by refraction seismics with other methods. A special resistivity cable for pole-dipole measurements on the sea-floor, with 10 m betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Thus, comparisons between apparent resistivity pseudo-sections are possible only for a given electrode array configuration. In order to restrict misinterpretation due to graphic representation, Lile et al (1994) proposed to move the data points according to an a priori knowledge of the sounding body, while Ritz et al (1999) proposed to use a filtering process. Nevertheless, comparisons between surveys done by different arrays are feasible if we are able to assign a ''real'' resistivity value to each point in the survey area.…”
Section: Apparent Resistivitymentioning
confidence: 99%
“…Thus, comparisons between apparent resistivity pseudo-sections are possible only for a given electrode array configuration. In order to restrict misinterpretation due to graphic representation, Lile et al (1994) proposed to move the data points according to an a priori knowledge of the sounding body, while Ritz et al (1999) proposed to use a filtering process. Nevertheless, comparisons between surveys done by different arrays are feasible if we are able to assign a ''real'' resistivity value to each point in the survey area.…”
Section: Apparent Resistivitymentioning
confidence: 99%
“…To date, ERT has been used for land areas and for shallow water areas (e.g., Allen & Merrick, 2007;Inoue, 2005;Lile et al, 1994) and even for deep water areas (Goto et al, 2008). For ERT survey, an electrical current is passed through two electrodes.…”
Section: Methods Of Marine Electrical Resistivity Tomographymentioning
confidence: 99%
“…Lile et al . () concluded that severely fractured zones, which may cause difficulties for tunnel construction, can be detected with seafloor arrays using electrodes inside a tunnel. Another ERT application in case of intunnel mining prospection was made by van Schoor and Binley () who studied the applicability of tunnel‐to‐tunnel ERT for imaging disruptive geological structures ahead of mining in an igneous platinum mining environment.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that performing small-scale resistivity tomography between the boreholes yields a better image of the geological setting and by which the operator could be better prepared. Lile et al (1994) concluded that severely fractured zones, which may cause difficulties for tunnel construction, can be detected with seafloor arrays using electrodes inside a tunnel. Another ERT application in case of intunnel mining prospection was made by van Schoor and Binley (2010) who studied the applicability of tunnel-to-tunnel ERT for imaging disruptive geological structures ahead of mining in an igneous platinum mining environment.The present study deals with the case of ERT measurements obtained in a combined mode using electrodes on surface and in-tunnel.…”
mentioning
confidence: 99%